Male hypogonadism in patients on maintenance hemodiafiltration: prevalence and therapeutic effect - Carvalho, Marcia S.; Torres, Raissa C.; Toniasso, Isabela M.; Magalhães, Andrea O.; Borges, Cynthia M.; Rocha, Erica P.; Kojima, Christiane A.; Elias, Rosilene M. (Frontiers in Endocrinology, 2026)
AimsMale hypogonadism is highly prevalent among patients undergoing dialysis and carries significant clinical implications, although is often overlooked. Testosterone deficiency in this population is associated with adverse clinical outcomes, mainly because of cardiovascular disease, protein energy wasting and infection complication. Therefore, identify these patients is a high clinical priority.MethodsThis is a cross-sectional study that enrolled adult men on maintenance hemodiafiltration in four dialysis centers. Hypogonadism was defined by two consecutive measurements of serum total testosterone levels. Free testosterone was calculated based on serum albumin and sex hormone-binding globulin. Symptoms of androgen deficiency were evaluated using androgen deficiency in aging males (ADAM) questionnaire. The presence of comorbidities and laboratory markers was also evaluated.ResultsHypogonadism was identified in 59 out of 121 patients (48.7%). Patients with hypogonadism were older (62 ± 15 vs. 57 ± 15 years, p < 0.001) and had higher prolactin levels (22 [13–36] vs. 14 [10–18] ng/mL, p = 0.002). No other significant difference was observed in demographic, clinical, or laboratory features between patients with and without hypogonadism. Among the 16 patients who received testosterone supplementation, 66.7% showed improvement in ADAM scores, with the median score decreasing from 3 (2–4) to 1 (0–2) (p = 0.003).ConclusionMore than one-third of men undergoing hemodiafiltration were diagnosed with hypogonadism. Aside from older age, no other distinguishing characteristics were identified in this population. Therefore, routine assessment of testosterone levels should be considered for all men undergoing dialysis. Further studies are needed to determine whether hormone supplementation can improve clinical outcomes.